Quantitative Assessment of Apically Extruded Debris after Single-Files Supplemental Retreatment considering Apical Patency Influence: In Vitro Study - Neveen Ali Shaheen; Nahla Gamaleldin Elhelbawy; Dalia Abdelhamid Sherif (International Journal of Biomaterials)
Objective. This study aims to assess the impact of re-establishing apical patency on the quantity of debris extruded through the apex after three supplementary retreatment files (TruNatomy (TRN), WaveOne Gold (WOG), and XP endo Finisher R (XPFR)). Materials and Methods. Eighty single-rooted mandibular premolars were prepared with ProTaper Universal rotary systems (PTU) up to F3 and obturated. The samples were divided into two main groups according to the presence or absence of the apical patency (n = 40), GI with apical patency and GII without apical patency. Based on the file system, which was adopted to eliminate the previous filling, each group had four subgroups (n = 10). In GI PTUR and GII PTUR, ProTaper Universal retreatment files (PTUR) were utilized only to remove the most primary filling material (control groups). In the other groups (PTUR) used, it was first followed by supplementary files. The quantity of debris extruded by different retreatment file systems was determined and compared to the corresponding control group with or without apical patency. Data were analyzed using a two-way ANOVA with a post hoc Tukey’s multiple comparison test at a 5% significance level. Results. There was a statistically significant difference among the control and experimental groups. XPFR had the least quantity of extruded debris. Apical patency did not affect the debris extrusion. Conclusion. All tested files led to a significant apical debris extrusion regardless of apical patency.